2022
DOI: 10.21203/rs.3.rs-1235572/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Two Different Uses of Underbody Forced-air Warming Blankets for the Prevention of Hypothermia in Patients Undergoing Arthroscopic Shoulder Surgery: a Prospective Randomized Study

Abstract: Background: Forced-air warming (FAW) is an effective method of preventing inadvertent perioperative hypothermia (IPH). However, its warming effects can be influenced by the style and position of the FAW blanket. This study aimed to compare the effects of underbody FAW blankets being placed under or over patients in preventing IPH.Methods: Patients (n=100) undergoing elective arthroscopic shoulder surgery in the lateral decubitus position were randomized into either under body (UB) group or the over body (OB) g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus, many medical specialty societies have provided guidelines for hypothermia prevention, which recommend monitoring the patient's body temperature and providing active warming interventions throughout the perioperative period [7,8]. However, despite the development of some effective active warming techniques, such as forced-air warming systems, self-warming mattresses, and irrigation and infusion of warmed fluids [9][10][11][12], a survey of 6 Asia-Pacific countries showed that compliance with international perioperative temperature management guidelines in the Asia-Pacific remains poor, especially in small hospitals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many medical specialty societies have provided guidelines for hypothermia prevention, which recommend monitoring the patient's body temperature and providing active warming interventions throughout the perioperative period [7,8]. However, despite the development of some effective active warming techniques, such as forced-air warming systems, self-warming mattresses, and irrigation and infusion of warmed fluids [9][10][11][12], a survey of 6 Asia-Pacific countries showed that compliance with international perioperative temperature management guidelines in the Asia-Pacific remains poor, especially in small hospitals [13].…”
Section: Introductionmentioning
confidence: 99%